The status of non-Muslims for giving evidence in the Islamic judicial system: past and present - Ramlee, Zulfakar (Serials Publications, 2010)
For imparting justice, it is an enevitable requirement for every party to bring evidence to support his case. The nature and scope of evidence to be produced in the court are very wide, and the most popular one is oral evidence to be given by a witness. Even documentary evidence, in most cases, needs the assistance of a witness to prove its genuineness. Moreover, in sophisticated types of evidence, such as forensic evidence, the role of an expert witness is very crucial. Thus, in countries like Malaysia, where the percentage of Muslims and the non-Muslims is approximately equal, the involvement of non-Muslim witnesses in the Syariah (It is the Malay version of Shari'ah) courts is inevitable and of great importance. Classical juristic views on the admissibility of testimony by non-Muslims need to be revisited. The next issue is the compellability of their attendance in the Syariah courts. The paper discussed this aspect of the Shari'ah law of evidence.